Mobile Learning: MIT App Inventor Mobile Programming – an experience carried out in Cape Verdean Higher Education - Alves Andrade Barbosa, Elizabeth (2022)
This article intends to report an experience of integrating new programming learning methodologies in higher education, which was conducted during the 2016/2017 school year, at the University of Cape Verde. This study was applied in two first-year classes of the electrotechnical engineering degree. These students used different mobile applications for learning to code which allowed them to work both inside and outside of the classroom. Among the applications used, MIT App Inventor has stood out as the favourite tool for the different activities developed for learning to code both individually and collaboratively. In this work, one presents the main uses of this tool during the above-mentioned academic year, in the curricular unit “Introduction to Programming”, describing some of the applications developed by the students, and also announcing some other applications used in this research.